Pengaruh Faktor Internal dan Eksternal terhadap Penyaluran Kredit Usaha Rakyat (KUR) bagi UMKM (Studi Kasus Pada PT. Bank Rakyat Indonesia Tahun 2011-2020) - Nur Kumala Sari; Niniek Imaningsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the internal and external factors that affect the distribution of KUR. The variables that are thought to have an effect on the distribution of KUR are interest rates, Capital Adequacy Ratio (CAR) and inflation. The data used is time series data, namely the distribution of BRI KUR in 2011-2020. This study uses a quantitative appoarch with analysis of hypothesis testing and descriptive analysis. The analysis technique used is multiple liniear regression. The results showed that the interest rate had a negative and significant effect on the distribution of KUR. CAR has a negative and significant effect on the distribution of KUR. Inflation has a negative and significant effect on the distribution of KUR. Interest rates, CAR and inflation together have a significant effect on the distribution of KUR.